A new “Bat-Voiced” species of Dendropsophus Fitzinger, 1843 (Anura, Hylidae) from the Amazon Basin, Brazil - Orrico, Victor G. D. (2014)
We describe Dendropsophus ozzyi sp. nov., a new species of treefrog, tentatively included in the Dendropsophus microcephalus Group and most notably diagnosed by the presence of pointed fingers and an advertisement call with a very high dominant frequency. The new species is known from three localities in the Brazilian Amazon forest, two on western State of Pará and one (the type locality) in eastern State of Amazonas (03°56’50”S and 58°26’36”W, 45 m a.s.l.).